2008
DOI: 10.1111/j.1399-0039.2008.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Luminex donor‐specific crossmatches

Abstract: In Luminex bead-based screening assays, color-coded microspheres coated with human leukocyte antigens (HLA) are used to identify both complement-binding and non-complement-binding HLA class I and II antibodies in recipient sera. Many laboratories rely on their specificity detection and use the information obtained for allocation of donor organs. A donor-specific crossmatch in the Luminex technique (LumXm) is for that reason desirable. A LumXm, in which the actual donor HLA are coated onto specific capture bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 23 publications
8
52
3
Order By: Relevance
“…This high sensitivity of SPA may be related in part to the cut-off level fixed at 500 MFI according to the manufacturer's criteria. Indeed recent studies have reported a higher cut-off value [12][13][14].…”
Section: Discussionmentioning
confidence: 96%
“…This high sensitivity of SPA may be related in part to the cut-off level fixed at 500 MFI according to the manufacturer's criteria. Indeed recent studies have reported a higher cut-off value [12][13][14].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown a good correlation between lysate crossmatch and Luminex antibody screening PRA and SAB tests in detecting HLA-A, B and DR DSA [43,44]. However the use of lysate crossmatch is currently restricted by its low sensitivity to detect DQ and DP DSA [43,44].…”
Section: Luminex Antibody Analysis and Luminex Lysate Crossmatchmentioning
confidence: 96%
“…However the use of lysate crossmatch is currently restricted by its low sensitivity to detect DQ and DP DSA [43,44]. Lysate crossmatch has several advantages compared with CDC crossmatch, in that (1) lysate can be stored long term and thus it is especially useful for post-transplantion monitoring; (2) it detects only anti-HLA IgG DSA, so it prevents false-positive results caused by irrelevant antibodies; and (3) it may detect rare HLA antigens because the sensitivity does not rely on bead panel but is specific to the organ donor antigens.…”
Section: Luminex Antibody Analysis and Luminex Lysate Crossmatchmentioning
confidence: 99%
“…After addition of a IgG-phycoerythrin conjugated secondary antibody, fluorescence is read using the Luminex instrument. Billen et al [46] reported, for the first time, a study on donor-specific Luminex crossmatch. Results obtained were compared with those of flow cytometry crossmatch, performed on the same donor-recipient pairs.…”
Section: Virtual and Luminex Crossmatchmentioning
confidence: 98%